Assessment of the impact of implementation of a zero blood alcohol concentration law in Uruguay on moderate/severe injury and fatal crashes: a quasi‐experimental study. (24th September 2020) - Davenport, Steven; Robbins, Michael; Cerdá, Magdalena; Rivera‐Aguirre, Ariadne; Kilmer, Beau
Abstract: Background and aims: Debates regarding lowering the blood alcohol concentration (BAC) limit for drivers are intensifying in the United States and other countries, and the World Health Organization recommends that the limit for adults should be 0.05%. In January 2016, Uruguay implemented a law setting a zero BAC limit for all drivers. This study aimed to assess the effect of this policy on the frequency of moderate/severe injury and fatal traffic crashes. Design: A quasi‐experimental study in which a synthetic control model was used with controls consisting of local areas in Chile as the counterfactual for outcomes in Uruguay, matched across population counts and pre‐intervention period outcomes. Sensitivity analyses were also conducted. Setting: Uruguay and Chile. Cases: Panel data with crash counts by outcome per locality‐month (2013–2017). Intervention and comparator: A zero blood alcohol concentration law implemented on 9 January 2016 in Uruguay, alongside a continued 0.03 g/dl BAC threshold in Chile. Measurements: Per‐capita moderate/severe injury (i.e. moderate or severe), severe injury and fatal crashes (2013–2017). Findings: Our base synthetic control model results suggested a reduction in fatal crashes at 12 months [20.9%; P ‐value = 0.018, 95% confidence interval (CI) = −0.340, −0.061]. Moderate/severe injury crashes did not decrease significantly (10.2%, P  = 0.312, 95% CI = −0.282, 0.075). The estimated effect at 24 months was smaller and with larger confidence intervals for fatal crashes (14%; P  = 0.048, 95% CI = −0.246, −0.026) and largely unchanged for moderate/severe injury crashes (−9.4%, P  = 0.302, 95% CI = −0.248, 0.058). Difference‐in‐differences analyses yielded similar results. As a sensitivity test, a synthetic control model relying on an inferior treatment–control match pre‐intervention (measured by mean squared error) yielded similar‐sized differences that were not statistically significant. Conclusions: Implementation of a law setting a zero blood alcohol concentration threshold for all drivers in Uruguay appears to have resulted in a reduction in fatal crashes during the following 12 and 24 months.